Novel time-synchronized immune-guided partial tumor irradiation: proof of principle trial - Tubin, Slavisa; Ashdown, M. L.; Ahmed, M. M.; Guha, C.; Salerno, G.; Celedin, B.; Trummer, B.; Demschar, S.; Raunik, W. (Radiotherapy and oncology, 2024)
Background and purpose - Radiotherapy for bulky tumors often results in palliation with suboptimal outcomes. The prognosis is worsened by immunosuppression caused by radio-chemotherapy, negatively impacting on survival. Novel Partial Tumor Irradiation (PTI) was designed to spare the Peritumoral Immune Microenvironment (PIM) and to be delivered synchronously with immune activity peaks, thus enhancing both local and distant tumor control through immunostimulation. - Materials and methods - Present proof-of-principle trial enrolled 26 patients with bulky tumors, comparing outcomes between treatments administered at immune activity peaks versus troughs. The primary endpoint was local-bystander and distal-abscopal response-rate. Secondary endpoints included overall-, progression-free-, cancer-specific survival, neoadjuvant and immunomodulatory potential. - Results - All measured outcomes were significantly influenced by treatment-timing. The bystander and abscopal response rates were 77% and 41%, respectively. PTI significantly upregulated pro-inflammatory and cell-death-inducing pathways improving the efficacy of radiotherapy by highly complex tumors. - Conclusions - This study highlights the profound impact PTI can have on a highly palliative patient cohort previously deemed beyond therapeutic hope. With 41 % of these patients still alive after a median follow-up of 50 months, PTI offers a potential lifeline for those facing advanced, treatment-resistant cancers. This approach generated also distant immunogenic anti-tumor responses, offering a promising new avenue for the treatment of advanced cancers.
Online veröffentlicht: 26. Juli 2024, Artikelversion: 31. Juli 2024
Gesehen am 19.05.2025